Mahdi Akhavān-Sāles and the issue in the language of Nimā's poetry - Mehrdad Zarei; Mohammad Shadrooymanesh (مطالعات زبانی و بلاغی)
Nimā Yushij's comprehensive look at poetry and the understanding that any change in poetry must be fundamental and general, prompted all elements in Nimā's "free verse" to undergo a fundamental transformation. Compared to classical poetry, one of the elements that underwent significant change in Nimā's free verse poetry was "language". The issue of language in Nimā's poetry has been the concern of his supporters and the excuse for his opponents since the beginning. Mahdi Akhavān-Sāles was an advocate of Nimā who sought to resolve the complexities and difficulties of his language and wrote the first independent book about the language of Nimā's poetry. This research initially deals with the opinions of Nimā's supporters and opponents regarding the language of his poetry. Then Akhavān's ideas in his book (Atā va laqāye Nimā Yushij) are analyzed using the "critical analysis" method. The study clarifies that Akhavān has tried to defend Nimā's style by finding analogies from the classic poetry for Nimā's language deviations in order to prove that Nimā has used most of the permissions and facilities available to his predecessors. Despite some mistakes, he has also pointed out some subtle points in his discussions, which were later expanded and completed by later researchers.